Study of meteoroid stream identification methods - Rudawska, Regina; Jopek, Tadeusz J. (Cambridge University Press, 2010)
We have tested the reliability of various meteoroid streams identification methods. We used a numerically generated set of meteoroid orbits (a stream component and a sporadic background) that were searched for streams using several methods.
Keywords: meteoroids; data analysis